2016
DOI: 10.4067/s0718-221x2016005000063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weathering on wood treated with tall oil combined with some additives

Abstract: Growing interest on bio-based material has led to focus on environmentally benign wood treatment systems because of the environmental concerns. Tall oil is a by-product from pulp and paper industry, contains resin and fatty acids, and is biodegradable. Tall oil treated wood can provide some reduction in water uptake and increase in decay resistance. In this research crude tall oil was dissolved in ethanol at 5, 10 and 15 % concentrations in the treatment of Scots pine according to full cell process. Dyestuff, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Positive values show the tendency of a composite surface to become reddish for Δa* and yellowish for Δb*, and negative values represent greenish for Δa* and bluish for Δb*. 35,36 Negative Δa* values were obtained in SMA and 10%UT samples, while positive values were obtained in other variations. The highest Δa* values were obtained in both UT and T samples in 30 wt% samples.…”
Section: Color Changementioning
confidence: 97%
“…Positive values show the tendency of a composite surface to become reddish for Δa* and yellowish for Δb*, and negative values represent greenish for Δa* and bluish for Δb*. 35,36 Negative Δa* values were obtained in SMA and 10%UT samples, while positive values were obtained in other variations. The highest Δa* values were obtained in both UT and T samples in 30 wt% samples.…”
Section: Color Changementioning
confidence: 97%
“…Investigations made with Tall Oil indicate its potential as a protective agent for wood. Those surveyed who focused on the search for an alternative as a preservative for wood in Tall Oil indicated that the preventive effect is related to the hydrophobic properties, with the high concentration of oleic acid, with the presence of unsaponifiables, with the stability when the acidity index and the saponification index [9,[46][47][48][49][50][51][52][53]. These factors may be indicative of increased resistance to biodeterioration to a greater or lesser degree.…”
Section: Tablementioning
confidence: 99%
“…It has been reported that linseed and tung oil are very efficient in protecting wood surface against water uptake [ 139 ]. Tall oil treatment was not found resistant to accelerated weathering when used alone in Scots pine wood, but in combination with iron oxide, it was found to be effective in reducing the weathering degradation of the wood surface [ 140 ]. The natural oils can be modified by introducing new groups to the fatty acid chains to cause the oils to react with the substrate or to increase the compatibility with a potential top coating [ 70 ].…”
Section: Treatments Of Wood With Inorganic Metal Compounds and Bio-based Water Repellentsmentioning
confidence: 99%